Spain’s Commitment to Lebanon: a New Role for Spain in the Near East? - Amaia Goenaga Sánchez (Revista CIDOB d'Afers Internacionals, 2007)
In summer 2006, Lebanon suffered the consequences of the open warfare between Israel and the Shi’ite organisation Hezbollah. Within this context, the Spanish government, together with the governments of some of its neighbouring countries, made an attempt to resolve the conflict. This commitment also became consolidated during the monthsfollowing the period of military conflict, and through three lines of action: a large-scale military contribution in the context of the UN Security Council’s Resolution 1701, the sending of economic aid to help rebuild the country and, finally, by intensifying politicalrelations with Lebanon. This shift in policy is significant if we bear in mind the previous weakness of relations between the two countries; however, we can see that this deployment of resources did not have so much to do with Lebanon itself as it did with Spain’s owninterests. In this sense, we can understand that the crisis has been turned into a platform for the practical application of the main lines that determine the socialist government’s external action.